A carbon dot-based nanoscale covalent organic framework as a new emitter combined with a CRISPR/Cas12a-mediated electrochemiluminescence biosensor for ultrasensitive detection of bisphenol A. Issue 6 (1st March 2023) - Ma, Rongxian; Jiang, Jiaxuan; Ya, Yanfei; Lin, Yu; Zhou, Yuyi; Wu, Yeyu; Tan, Xuecai; Huang, KeJing; Du, Fangkai; Xu, Jingjuan
Abstract : Fabrication of a carbon dot-based covalent organic framework as a novel ECL emitter combined with the sensing strategy mediated by CRISPR/Cas12a to construct an ECL biosensor for ultrasensitive detection of BPA. Abstract : Exploring new highly efficient electrochemiluminescence (ECL) luminophores is a necessary condition for developing ultrasensitive ECL biosensors. Therefore, a luminescent carbon dot-based covalent organic framework (CD-COF) was prepared using aldehyde-based carbon dots (CDs) and 1, 3, 5-tris (4-aminophenyl) benzene (TPB). Because the CD-COF made the regular arrangement of CDs conducive to improving the ECL response, CD-COF had a higher ECL intensity and efficiency than CDs. What's more, the ECL intensity of the CD-COF/S2 O8 2− /Bu4 N + system was about 2.98, 7.50, and 28.08 times higher than those of the CD-COF/S2 O8 2−, CDs/S2 O8 2− and S2 O8 2− systems, respectively. Considering the remarkable ECL performance, the CD-COF/S2 O8 2− /Bu4 N + system was employed combined with the CRISPR/Cas12a trans-cutting strategy to construct an "off–on" ECL biosensor for BPA detection. The proposed ECL biosensor exhibited excellent performance with a wide linear range from 1.0 × 10 −14 mol L −1 to 1.0 × 10 −5 mol L −1 with a low detection limit of 2.21 fM (S/N = 3) under the optimized conditions. The biosensor demonstrated that CD-COF can be used as an efficient ECL emitter, thus expanding the application field of COFs. In addition, the good stability and specificity of the biosensor enabled the rapid detection of BPA, which will provide valuable insights into promising ultrasensitive ECL biosensors.